Bioprospecting Of Moringa & Its Prophylactic Activities - Shilpa Mohan Shitole; Ms. Pradnya Bansode; Jalindarnath Gajendra Bagal; Marina Albuquerque; Ruchita Shrivastava (Revista Electronica de Veterinaria, 2024)
Bioprospecting of Moringa oleifera, a plant having massive nutritional and medicinal properties, exposed the remarkable prophylactic activities, especially against microbial attacks. Extensive phytochemical composition in Moringa attributes to therapeutic values as vitamins, minerals, bioactive flavonoids, alkaloids, and phenolics, among many others—traits known for their antioxidant, anti-inflammatory, and antimicrobial properties. It has been shown to have antimicrobial activity against some pathogenic bacteria, fungi, and viruses, stating well its effectiveness in both prevention and treatment of infections. Besides, Moringa displays an array of prophylactic activities supporting total health and preventing all occupational chronic diseases like CVDs, diabetes, and cancer. The use of Moringa in dietary and therapeutic formulations, therefore, represents that natural and sustainable pathway to the enhancement of health and the fight against microbial resistance. It provides a review of the current research concerning the prophylactic and antimicrobial activities of Moringa oleifera, outlining the possibility that it could greatly be valued as a resource in the development of new preventive health solutions.